Correlation Between Body Mass Index, Blood Pressure, Uric Acid, Total Cholesterol Levels and Age - Siagian, Ernawaty (Fakultas Ilmu Keperawatan Universitas Klabat, 2026)
Obesity increases blood pressure, thereby increasing the risk of heart disease and is recognized as a major factor in the development of hypercholesterolemia and increased uric acid levels. This study aimed to evaluate the relationship between Body Mass Index (BMI), serum uric acid levels, total cholesterol, systolic and diastolic blood pressure, and age. Using a purposive sampling method, 49 respondents participated in a descriptive correlation study. Blood sample analysis was performed to determine total cholesterol and uric acid levels, as well as blood pressure and body mass index (BMI) measurements. Univariate and bivariate analyses based on correlation tests were part of the analytical strategy. A significant relationship of 0.014 < 0.05 between gender and cholesterol was observed. Age and systolic blood pressure variables were statistically significant (p < 0.05). The statistical significance of systolic and diastolic blood pressure was determined at 0.000 < 0.05. With a significance value of 0.006 < 0.05, there was a statistically significant relationship between diastolic blood pressure and body mass index. The statistical significance of uric acid and age was found to be 0.040 < 0.05. Managing lifestyle and maintaining a healthy weight are crucial in preventing hyperuricemia, high blood pressure, and lipid abnormalities. Obesitas meningkatkan tekanan darah sehingga meningkatkan risiko penyakit jantung dan diakui sebagai faktor utama dalam perkembangan hiperkolesterolemia dan peningkatan kadar asam urat. Penelitian ini bertujuan untuk mengevaluasi hubungan antara Indeks Massa Tubuh (IMT), kadar asam urat serum, kolesterol total, tekanan darah sistolik dan diastolik, serta usia. Dengan menggunakan metode sampling purposif, 49 responden berpartisipasi dalam studi korelasi deskriptif. Analisis sampel darah dilakukan untuk menentukan kadar kolesterol total dan asam urat, serta pengukuran tekanan darah dan indeks massa tubuh (IMT). Analisis univariat dan bivariat berdasarkan uji korelasi menjadi bagian dari strategi analitis. Hubungan yang signifikan sebesar 0,014 < 0,05 antara jenis kelamin dan kolesterol diamati. Variabel usia dan tekanan darah sistolik terbukti secara statistik signifikan (p < 0,05). Signifikansi statistik tekanan darah sistolik dan diastolik ditentukan sebesar 0,000 < 0,05. Dengan nilai signifikansi 0,006 < 0,05, terdapat hubungan yang signifikan secara statistik antara tekanan darah diastolik dan indeks massa tubuh. Signifikansi statistik asam urat dan usia ditemukan sebesar 0,040 < 0,05. Mengelola gaya hidup dan menjaga berat badan yang sehat sangat penting dalam mencegah hiperurisemia, tekanan darah tinggi, dan kelainan lipid.